HDI flexible front-end hybrid prototype for the PS module of the CMS tracker upgrade. (9th February 2017) - Kovacs, M.; Blanchot, G.; Gadek, T.; Honma, A.; Koliatos, A.
Abstract: The CMS tracker upgrade for the HL-LHC relies on different module types, depending on the position of the respective module. They are built with high-density interconnection flexible circuits that are wire bonded to silicon strip and pixel-strip sensors. The Front-End hybrids will contain several flip-chip bonded readout ASICs that are still under development. Mock-up prototypes are used to qualify the advanced flexible circuit technology and the parameters of the hybrids. This paper presents the Pixel-Strip (PS) mock-up hybrid in terms of testing, interconnection, fold-over, thermal properties and layout feasibility. Plans for circuit testing at operating temperature (-30 ̂ ) are also presented.